2010
DOI: 10.1007/s00726-010-0600-9
|View full text |Cite
|
Sign up to set email alerts
|

Manganese superoxide dismutase: beyond life and death

Abstract: Manganese superoxide dismutase (MnSOD) is a nuclear-encoded antioxidant enzyme that localizes to the mitochondria. Expression of MnSOD is essential for the survival of aerobic life. Transgenic mice expressing a luciferase reporter gene under the control of the human MnSOD promoter demonstrate that the level of MnSOD is reduced prior to the formation of cancer. Overexpression of MnSOD in transgenic mice reduces the incidences and multiplicity of papillomas in a DMBA/TPA skin carcinogenesis model. However, MnSOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 218 publications
(270 reference statements)
2
82
0
4
Order By: Relevance
“…Along with our in vitro data (346) on cytoxic effects of MnPs through H 2 O 2 production when combined with ascorbate, several other groups reported that overexpression of MnSOD kills tumors through H 2 O 2 production (101,130,152,190). We hope that future studies will provide deeper insight into anti-vs. prooxidative actions of compounds (endogenous or exogenous) that are presently primarily considered antioxidants.…”
Section: Cancersupporting
confidence: 72%
See 1 more Smart Citation
“…Along with our in vitro data (346) on cytoxic effects of MnPs through H 2 O 2 production when combined with ascorbate, several other groups reported that overexpression of MnSOD kills tumors through H 2 O 2 production (101,130,152,190). We hope that future studies will provide deeper insight into anti-vs. prooxidative actions of compounds (endogenous or exogenous) that are presently primarily considered antioxidants.…”
Section: Cancersupporting
confidence: 72%
“…Breast cancer. Because (a) MnSOD (the essential endogenous antioxidant) is reduced in many cancers; (b) increased expression of MnSOD inhibits cancer growth (152), and (c) SOD mimic, MnTE-2-PyP 5þ enters mitochondria (306), it is only logical that we tested the possible anticancer activity of MnTE-2-PyP 5þ . Three studies from our group were done within the last 8 years (with doses of MnTE-2-PyP 5þ ranging from 6 to 15 mg=kg) with the goal to prove if and why a catalytic SOD mimic=peroxynitrite scavenger would exert anticancer effects [i.e., to evaluate whether the attenuation of the oxidative stress by MnTE-2-PyP 5þ could suppress tumor growth in a 4T1 mouse breast tumor model (222,221,259)].…”
Section: Cancermentioning
confidence: 99%
“…Furthermore, Mn-SOD influences the activity of transcription factors (such as HIF-1α, AP-1, NF-κB and p53) and affects DNA stability [35]. A critical role of Mn-SOD under physiological and pathological conditions has recently been reviewed in details and the following findings of Mn-SOD confirm the critical role of Mn-SOD in the survival of aerobic life [36][37][38][39]:…”
Section: Superoxide Dismutase In Biological Systemsmentioning
confidence: 85%
“…Disruption of the MnSOD gene in mice has been -toc: -tocoferol; Cyt c3+ (reduced cytochrome c) ; CuZnSOD: copper-zinc superoxide dismutase; Gpx: glutathione peroxidase; GSH: reduced glutathione, GSSG: oxidized glutathione; L-Arg: L-arginine; mtNOS: mitochondrial nitric oxide synthase, NO: nitric oxide; Prx3-(SH) 2 : peroxiredoxine 3 reduced, Prx3-S 2 : peroxiredoxine 3 oxidized; ROS: reactive oxygen species, RNS: reactive nitrogen species; Trx2-(SH) 2 : tioredoxine 2 reduced, Trx2-S 2 : tioredoxine oxidized. associated with early postnatal lethality (Li et al, 1995), while MnSOD overexpression was shown to protect mitochondrial function and block apoptosis (Holley et al, 2010). The activity of MnSOD should be coordinated with H 2 O 2 -removing enzymes.…”
Section: Enzymatic Antioxidantsmentioning
confidence: 99%